Proceedings of 5th International Conference on Recent Advances in Space Technologies - RAST2011 2011
DOI: 10.1109/rast.2011.5966808
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation index based technique for global agricultural drought monitoring

Abstract: Droughts occurring every year all over the world have great impacts on human society, nature, and the global economy for example in declining crop yields, reduction of water supplies, and distressed vegetation. Satellite data have been widely used in drought monitoring. Vegetation condition is an excellent indicator of agricultural drought and can be quantified by the Normalized Difference Vegetation Index (NDVI). One way to detect agricultural drought is to quantify it through calculation of drought indices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…Drought indices are particularly useful for monitoring the impact of climate variability on vegetation because the spatial and temporal identification of drought episodes is extremely complex. A number of drought indices, including meteorological (Wilhite and Glantz, 1985), remote sensed, hydrological and other indicators, have been used to measure drought impacts (Palmer, 1965(Palmer, , 1968Gibbs and Maher, 1967;Shafer and Dezman, 1982;Kogan, 1990Kogan, , 2002McKee et al, 1993;Keyantash and Dracup, 2004;Bhuiyan et al, 2006;Yagci et al, 2011;Zhou et al, 2012;Du et al, 2013;Yang et al, 2013;Abbas et al, 2014;Nichol and Abbas, 2015). Traditional methods of drought assessment and monitoring rely on rainfall data (e.g., the Palmer drought severity index (PDSI) and Standardized Precipitation Index (SPI)).…”
Section: Introductionmentioning
confidence: 99%
“…Drought indices are particularly useful for monitoring the impact of climate variability on vegetation because the spatial and temporal identification of drought episodes is extremely complex. A number of drought indices, including meteorological (Wilhite and Glantz, 1985), remote sensed, hydrological and other indicators, have been used to measure drought impacts (Palmer, 1965(Palmer, , 1968Gibbs and Maher, 1967;Shafer and Dezman, 1982;Kogan, 1990Kogan, , 2002McKee et al, 1993;Keyantash and Dracup, 2004;Bhuiyan et al, 2006;Yagci et al, 2011;Zhou et al, 2012;Du et al, 2013;Yang et al, 2013;Abbas et al, 2014;Nichol and Abbas, 2015). Traditional methods of drought assessment and monitoring rely on rainfall data (e.g., the Palmer drought severity index (PDSI) and Standardized Precipitation Index (SPI)).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural drought monitoring strictly requires spatially contiguous time series data to predict the surface temperature and vegetation condition, which climate-based indices have main drawbacks (Yagci et al, 2011;Tonini et al, 2012). Hence, data from remote sensing image at high temporal even at low spatial resolution can aid to assist in monitoring crop failures as they provide crucial information in near-real time over large areas as opposed to a single point measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The VCI value covers 16 days after the ith day. Numerous studies have demonstrated its ability to identify droughts at the regional (Liu and Kogan 1996;Yagci et al 2011aYagci et al , 2011b and global scale (Kogan 1993(Kogan , 1997(Kogan , 2001Unganai and Kogan 1998;Yagci et al 2012). …”
Section: Vegetation Condition Indexmentioning
confidence: 99%